A comparison of methodologies for the non-invasive characterisation of commercial Li-ion cells. (May 2019) - Barai, Anup; Uddin, Kotub; Dubarry, Matthieu; Somerville, Limhi; McGordon, Andrew; Jennings, Paul; Bloom, Ira
Abstract: Lithium-ion cells currently power almost all electronic devices and power tools; they are a key enabling technology for electric vehicles and are increasingly considered to be the technology of choice for grid storage. In line with this increased applicability, there is also an increase in the development of new commercial lithium-ion cell technologies that incorporate innovative functional components (electrode material compositions and electrolyte formulations) and designs, leading to a diverse range of performance characteristics. The uniqueness of each technology in-turn gives rise to unique evolutions of cell performance as the cell degrades because of usage. Non-destructively measuring and subsequently tracking the evolution of lithium-ion cell characteristics is valuable for both industrial engineers and academic researchers. To proceed in this regard, stakeholders have often devised their own procedures for characterising lithium-ion cells, typically without considering unification, comparability or compatibility. This makes the comparison of technologies complicated. This comprehensive review for the first time has analysed and discusses the various international standards and regulations for the characterisation and electrical testing of lithium-ion cells, specifically for high-power automotive and grid applications.